Analisis Strategi Guru Dalam Menanamkan Nilai Pendidikan Karakter Disiplin Siswa Kelas V SDN 145 Randanan - Novalia Sulastri (LPPM UKI Toraja, 2022)
Discipline character is very important to be instilled in students. At SDN 145 Randanan has instilled the value of discipline. Such as carrying out picket duties, greetings, participating in flag ceremonies. This is indicated by the teacher's efforts to provide sanctions for violations of school rules and regulations committed by students. However, there are still some students who violate the rules including: students are often late for school, students do not put in their uniforms, students are not fully clothed during the ceremony. Therefore, it is important for a teacher to know what strategies are used to instill the value of character education in students. This study aims to determine how the teacher's strategy in instilling the value of character education in class V SDN 145 Randanan This research approach is a qualitative approach with this type of research. qualitative descriptive. The types of data used are primary and secondary data with data sources from informants or sources, books, and scientific journals. Data collection techniques used, namely observation, interviews, and documentation with data analysis using data reduction, data presentation, and drawing conclusions. The results showed that the teacher's strategy in instilling the value of disciplined character education in fifth grade students of SDN 145 Randanan was to be an example and role model, habituation, awareness, giving rewards (gifts), educative punishments (educating), setting school rules and class rules.